2018
DOI: 10.1111/ijpo.12278
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular remodelling and vascular adaptive changes in adolescents with obesity

Abstract: Obesity causes alterations in myocardial mechanics with preserved V-A in children. These findings may aid intervention in preventing the long-term cadiovascular effects of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Notably, adjustment for BMI along with CRF attenuated the secular trends to a larger degree than did attenuation by CRF per se for AMI and HF. The contrasting trends for AMI and HF make sense considering the mounting evidence for a stronger link between obesity and cardiac remodelling compared with the link between obesity and AMI in younger people [15,16,39]. Moreover, it is clear that the impacts of some conventional risk factors on the decline are far greater for AMI than for HF [2], such that cholesterol and smoking are less associated with incident HF, whereas BMI [39] or triglycerides [14] are stronger risk factors for HF.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, adjustment for BMI along with CRF attenuated the secular trends to a larger degree than did attenuation by CRF per se for AMI and HF. The contrasting trends for AMI and HF make sense considering the mounting evidence for a stronger link between obesity and cardiac remodelling compared with the link between obesity and AMI in younger people [15,16,39]. Moreover, it is clear that the impacts of some conventional risk factors on the decline are far greater for AMI than for HF [2], such that cholesterol and smoking are less associated with incident HF, whereas BMI [39] or triglycerides [14] are stronger risk factors for HF.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated MH is closely associated with obesity and target-organ damage in adolescents ( 33 35 ). Moreover, obesity and higher plasma glucose level in youth has been found to be linked to decreased myocardial deformation even in the absence of comorbidities in early stages ( 24 , 36 38 ). Therefore, it is reasonable to indicate that the observation of reduction of strain in asymptomatic young MH patients may contribute to the comprehensive effects of higher ambulatory pulse rate and glucose level as well as body weight.…”
Section: Discussionmentioning
confidence: 99%
“…Although ventricular weight is typically normalized to body weight in experimental research, overweight subjects have lower ventricular mass/body weight ratio, yielding an artificial difference as a result of the increased denominator in obesity ( 265 ). Recent observations showed that patients with obesity displayed a higher LV mass when appropriately indexed to height 2.7 ( 266 ). LV mass indexed to height 2.7 is more appropriately employed to avoid misleading predictions of CVD risk in obesity.…”
Section: Cardiac Remodeling In Obesitymentioning
confidence: 99%